Pembenahan Posyandu dan Penerapan Go Green di Happy Garden - Ulfatul Aini; Sinta Nuriah (National Conference for Community Service Project (NaCosPro), 2019)
SEPORA activities are community service activities for Batam International University students. In the title of our article, which is improving the Posyandu and implementing go green in Happy Garden is a form of concern for comfort and the environment there. With the aim that the emergence of public awareness about the importance of greening, cleanliness, and care for their environment. With the hope that the surrounding community can continue to take the initiative to go green. the target of community service is the Happy Garden housing community in the Baloi Indah area of Batam. The stage that we do is hold a meeting with the head of the region what we can help to meet the needs of its citizens by conducting questions and answers and suggestions, then we conduct a field survey. The results of our community service activities gave satisfaction to residents of Happy Garden housing, we got good feedback from RW mothers and our work was truly satisfying. The Happy Garden posyandu looks new and is becoming green. I hope that the reforestation we provide can be maintained well and alive